Gross and functional analyses of the tensor fasciae suralis muscle with magnetic resonance imaging - Ethan L. Snow; Branden C. Fox; Hunter A. Eide; Matthew J. Vilburn (Translational Research in Anatomy)
Introduction: The tensor fasciae suralis (TFS) is a non-typical skeletal muscle that develops from one of the hamstring muscles and attaches to the deep fascia of the posterior leg (i.e., crural/sural fascia). By spanning the popliteal region, TFS can present as an unsuspected mass, impinge contiguous neurovasculature, complicate surgical access to posterior knee, and strain under typical use of the lower limb. Despite the necessary clinical discussion TFS generates, information about comparative gross anatomy examination, magnetic resonance imaging (MRI), and functional analyses of TFS is scarce in the literature. Therefore, the objective of the present study is to present a comprehensive report of a left unilateral TFS with gross imaging, detailed anatomical descriptions, MRI, biomechanical analysis, comparative review of published TFS cases, and discussion of clinical implications. Methods: A left unilateral TFS was discovered during routine human cadaver dissection. After initial discovery of its proximal segment, axial and sagittal T1-and T2-weighted MRI was performed to visualize the entire TFS and its relation to nearby structures. The entire TFS and contiguous anatomy were then dissected, carefully cleaned of extraneous fascia, and photographed in situ. Gross and microscopic architectural features of TFS were measured, and its maximal isometric force was calculated. Results: The 13.4 cm long, 5.02 g muscular belly of TFS branched 27.2° from the long head of biceps femoris and inserted into the investing fascia of the gastrocnemius medial head via a prominent 2.6 cm × 4.8 mm x 0.5 mm tendon. Gross imaging and MRI showed TFS crossing over the common fibular, tibial, and medial sural nerves. Biomechanical analysis determined TFS to be capable of producing 8.10 N of force. Conclusions: The course of TFS offers notable clinical discussion about distal motor and sensory loss resulting from compression-based lesions of the underlying nerves. MRI, paired with full gross imaging and biomechanical analyses, provides a catalog of comparative information on TFS that may aide in differential diagnosis of an unsuspected mass in the popliteal region and guide subsequent treatment.